Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) Gaya Hidup Berkelanjutan Fase E Di SMAN 22 Bandung - Sunandar, Aan; Mahmudah, Fitri Nur (Indo-MathEdu Intellectuals Journal, 2023)
In an era of evolving global dynamics, social, environmental, and economic challenges affect people's lives, especially youth. Senior High School (SMA) plays an important role in shaping the character of youth. Pancasila Youth supports sustainable development, and sustainable lifestyles are important for the environment and well-being. This article illustrates the importance of integrating Pancasila values and sustainable lifestyles in high school. On the other hand, understanding of this integration is still limited and practical implementation needs to be improved. Recent studies emphasize the need for character education and sustainable lifestyles in high school education. However, the gap between concept and practice still exists. This research uses a qualitative approach with in-depth interviews at SMAN 22 Bandung. The results showed the need for integration of Pancasila values and sustainable lifestyles in education. Despite challenges in implementation, the program encourages student participation and awareness of positive change. This research recommends developing a curriculum that integrates the values of Pancasila and sustainable lifestyles, in line with efforts to form a responsible young generation and contribute positively to society and the environment.